Welding rod for 9Ni steel for alternating current welding
By using fluoride-carbonate-tungsten oxide slag-type welding rods in 9Ni steel electrodes, the arc instability caused by excessive fluoride in AC welding is solved, and efficient hydrogen removal performance and welding stability are achieved, improving Welding quality and mechanical properties.
Patent Information
- Application Number
- CN202411510938.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing 9Ni steel welding rods have excessive fluoride content in AC welding, resulting in arc instability and affecting welding quality. Although traditional alkaline slag-based welding materials have increased fluoride content, they have led to a decrease in arc stability.
Using fluoride-carbonate-tungsten oxide slag-type welding rods, dilute welding pool, reduce diffusion hydrogen content and improve arc stability. The skin ingredients include 16%-20% fluoride, 20%-25% fluoride Carbonate, 1%-5% titanium oxide, etc., combined with pure nickel welding core, optimize welding performance.
The arc stability and good technical performance of welding at -196 degrees Celsius are achieved, which reduces the generation of hydrogen pores and improves the continuity and quality of welding.
Smart Images

Figure SMS_1 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal welding, in particular to a welding rod for 9Ni steel used for AC welding. Background Art
[0002] With the rapid development of global integration and industrialization, the demand for energy is increasing, and on the other hand, global warming is causing the demand for clean energy to increase. As natural gas becomes more and more important as a clean fuel, global natural gas production and consumption are growing rapidly. The transportation and storage of liquefied natural gas requires a large number of cryogenic storage tanks (LNG storage tanks). The working environment requires that the materials used to manufacture LNG storage tanks have good low-temperature toughness and good strength in low-temperature environments.
[0003] 9Ni steel is a medium alloy steel developed by the American International Nickel Company, with a structure of martensite plus bainite. This steel still has good low-temperature impact toughness, high strength and corrosion resistance when used at extremely low temperatures, and has low alloy content, low thermal expansion rate and good welding performance. Therefore, 9Ni steel has become one of the main materials for manufacturing LNG storage tanks.
[0004] In recent years, LNG technology has developed rapidly, and LNG storage tanks have basically achieved domestic design and manufacturing, which has greatly stimulated the demand for 9Ni steel and supporting welding materials. In the engineering application of LNG storage tanks, the most common welding rods are those for manual arc welding. However, this type of welding rod is still mainly imported. Domestic major welding material companies continue to develop domestic alternatives, but there is still a lot of gap with similar foreign welding materials. The main problem is to improve the mechanical performance indicators under the premise of reliable guarantee of the stable performance of AC welding. At present, one type of domestic welding rod is to ensure the performance of AC welding process by reducing the fluoride in the coating.
[0005] For example, CN106181115A discloses a nickel-based welding rod for low-splash 9Ni steel, comprising a welding core and a coating, wherein the coating components include, by weight percentage: 6-15% cryolite, 21-24% marble, 10-14% rutile, 2-8% silicon oxide, 2-7% strontium carbonate, 2-6% metallic molybdenum, 2-3% metallic manganese, 1-6% borax, and 05-3% seaweed salt.
[0006] CN113414519A discloses an ENi6620 nickel-based welding rod for alternating current, a preparation method thereof and a welding method thereof, comprising a welding core and a coating coated on the surface of the welding core, wherein the coating comprises: 6-10 parts by weight of marble, 3-6 parts by weight of strontium carbonate, 6-9 parts by weight of fluorite, 2-5 parts by weight of potassium ice crystal powder, 0.5-1.5 parts by weight of potassium fluoroborate, 2-6 parts by weight of rutile, 5-8 parts by weight of electrolytic manganese, 25-30 parts by weight of metallic chromium, 15-22 parts by weight of ferromolybdenum, 2-5 parts by weight of ferrotitanium, 3-6 parts by weight of tungsten powder, 5-9 parts by weight of ferroniobium, 1-3 parts by weight of soda ash, 2-6 parts by weight of potassium titanate, 1-4 parts by weight of rare earth fluoride, 0.5-2.5 parts by weight of zirconium dioxide and 0.5-3.5 parts by weight of rare earth ferrosilicon.
[0007] In these two patents, the fluoride content of CN106181115A is less than 15% (6-15% cryolite), and the fluoride content of CN113414519A is also less than 15% (6-9 parts by weight of fluorite, 2-5 parts by weight of potassium cryolite powder, 0.5-1.5 parts by weight of potassium fluoroborate). The fluoride in the coating plays a role in dehydrogenation, making the molten pool diffuse hydrogen lower, thereby ensuring good low-temperature mechanical performance indicators. Another domestic welding rod is to ensure mechanical performance indicators. The coating is alkaline slag system, with more carbonates and fluorides, but the AC weldability is not very stable.
[0008] In order to increase the fluoride content, CN111590240A discloses a nickel-based welding rod specially used for overhead welding with 9% Ni steel. The coating adopts a high-basicity CaCO3-MgCO3-CaF2 low-hydrogen slag system, and the coating components are: calcium carbonate 20-26%; magnesium carbonate 15-24%; calcium fluoride 10-15%; potassium cryolite 10-16%; sodium carbonate 0-1%; rutile 3-8%; metallic manganese 2-4%; rare earth ferrosilicon 2-5%; ferrotitanium 1-3%; aluminum powder 0.5-3.0%; molybdenum powder 10-15%; tungsten powder 2.5-4.0%; zirconium powder 1-4%; alginate 0.5-2.5%.
[0009] Although this patent greatly increases the fluoride content to more than 20% (calcium fluoride 10-15%; potassium cryolite 10-16%), the alkalinity is also high, and the carbonate content exceeds 35% (calcium carbonate 20-26%; magnesium carbonate 15-24%). Excessive carbonate makes the molten pool too intense during AC welding, and a large amount of fluoride aggravates the instability of AC welding. Because F ions are elements with high ionization potential, a large amount of F ions destroy the stability of AC.
[0010] The stability of the welding arc directly determines whether the welding process can proceed smoothly and continuously and affects the quality of the final weld. An unstable arc can easily cause poor fusion between the base material and the weld, resulting in defects such as pores and slag inclusions. The stability of the welding arc is generally related to the welding parameters, the performance of the welding material, and the characteristics and type of the welding power source.
[0011] It is well known that the stability of DC welding is significantly better than that of AC power supply, because during AC welding, the positive and negative poles change 50 times per second, and the current passes through the zero point 100 times per second. Each time the current passes through the zero point, the arc will be extinguished instantly, which will cause the electron emission and gas ionization to weaken, and easily cause arc instability. However, magnetic blow is easy to occur in 9Ni steel welding, so AC welding has to be used, so we must solve this problem by improving the characteristics of welding materials.
[0012] The arc stability of welding materials depends on their chemical composition. Different chemical elements have different ionization potentials. The smaller the ionization potential, the easier it is to ionize. Therefore, the more easily ionized elements and compounds contained in the welding material, the more stable the arc. Acidic slag welding materials are easy to perform AC welding because they contain more easily ionized substances. Alkaline slag contains more fluorides. Fluorine not only has a high ionization potential, but also has a strong affinity with electrons. It can capture electrons in the arc to form negative ions, reduce the number of electrons, and thus reduce the stability of the arc.
[0013]
[0014] In summary, we need to invent a welding material that contains a certain amount of fluoride to achieve better dehydrogenation performance and good technical indicators; but we cannot use the traditional alkaline slag system that results in too high a fluoride content, affecting the stability of AC welding. Summary of the invention
[0015] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and to provide a welding rod for 9Ni steel for AC welding, which can meet the requirements of AC welding of 9Ni steel and comply with various welding technical indicators.
[0016] It can achieve the goal of containing a certain amount of fluoride to achieve better dehydrogenation performance while obtaining good technical indicators; it overcomes the problem of excessively high fluoride content caused by traditional alkaline slag systems, which affects the stability of AC welding.
[0017] In order to achieve the purpose of the present invention, the technical solution adopted is:
[0018] A welding rod for 9Ni steel for AC welding, comprising a welding core and a coating.
[0019] The welding core part is a pure nickel welding core, and the coating part is composed of powder bonding;
[0020] The components of the powder are by weight:
[0021] 16%-20% fluoride;
[0022] 20%-25% carbonate;
[0023] 1%-5% titanium oxide;
[0024] 2%-6% potassium titanate;
[0025] 3%-5% tungsten powder;
[0026] 1%-3% tungsten oxide;
[0027] 1%-3% atomized ferrosilicon;
[0028] 1%-6% electrolytic manganese;
[0029] 5%-10% ferroniobium;
[0030] 10%-15% molybdenum powder;
[0031] 25%-28% metallic chromium;
[0032] 1%-5% iron powder;
[0033] 0.1%-0.6% graphite;
[0034] 1%-3% seaweed salt.
[0035] In a preferred embodiment of the present invention, the weight ratio of the coating to the electrode body is (3.5-4.5):10.
[0036] In a preferred embodiment of the present invention, the tungsten oxide is WO3, W20O58, W18O49, or WO2.
[0037] In a preferred embodiment of the present invention, the fluoride is any one or more of calcium fluoride, sodium fluoroaluminate, and potassium fluoroaluminate.
[0038] In a preferred embodiment of the present invention, the carbonate is any one or more of calcium carbonate, strontium carbonate, lithium carbonate and barium carbonate.
[0039] The beneficial effects of the present invention are:
[0040] When the welding rod of the present invention is used for AC welding, the AC arc stability is excellent, and the welding rod cladding metal has good technical properties at -196 degrees Celsius.
[0041] It can achieve the goal of containing a certain amount of fluoride to achieve better dehydrogenation performance while obtaining good technical indicators; it overcomes the problem of excessively high fluoride content caused by traditional alkaline slag systems, which affects the stability of AC welding. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the welding state of CN111590240A.
[0043] Figure 2 This is the state after welding of the present invention.
[0044] Figure 3 This is the weld effect diagram after slag removal of CN111590240A.
[0045] Figure 4 This is a welding seam effect diagram after slag removal according to the present invention. DETAILED DESCRIPTION
[0046] In order to meet the needs of manual arc welding of 9Ni steel for AC welding, the main differences between the present invention and the prior art are:
[0047] First, the coating of the welding rod in the present invention adopts a unique fluoride-carbonate-tungsten oxide slag system. The fluoride in the coating dilutes the welding molten pool, improves the fluidity of the nickel-based alloy welding molten pool, and is conducive to the overflow of harmful gases. At the same time, fluoride ions combine with hydrogen to reduce the diffusible hydrogen content in the molten pool and prevent the generation of hydrogen pores.
[0048] Second, the carbonate added in the present invention mainly plays the role of slag-making and gasification, while strontium carbonate and the like also have the ability to resist moisture absorption and can better reduce the diffusible hydrogen content of the molten pool.
[0049] Third, tungsten oxide (WOX) is added to the powder of the present invention, which has two functions: First, it increases the amount of fluoride added to the coating. Generally, the slag system will deteriorate AC welding with the increase of fluoride, because fluorine is an anti-ionizing substance that will seize electrons in the arc, while tungsten oxide will react before fluoride ions and protect the electrons in the arc. The specific reaction is as follows:
[0050] (Dehydrogenation reaction)
[0051] (Fluoride ion capture reaction)
[0052] Fourth, tungsten oxide has a high melting point, which can increase the high-temperature melting point of slag during welding, making the welding process in all positions better.
[0053] The functions of other components in the powder in the coating of the welding rod of the present invention are shown in Table 1 below:
[0054]
[0055]
[0056] Considering that the chemical composition of pure nickel welding core is mainly Ni element, in order to match the Ni-Cr-Mo alloy system used in 9Ni steel welding rod, other elements must be added to the coating.
[0057] Therefore, 3%-5% tungsten powder, 5%-10% ferroniobium, 10%-15% molybdenum powder, and 25%-30% metallic chromium are specifically added to the coating; at the same time, 1%-3% atomized ferrosilicon and 1%-6% electrolytic manganese are added to facilitate desulfurization and deoxidation.
[0058] In addition, 0.1%-0.6% of graphite is added to the coating to refine the transition droplets and reduce welding spatter. 1%-5% of iron powder improves the fluidity of the molten pool and improves the arc stability. 1%-3% of seaweed salt improves the pressure coating and improves the arc stability.
[0059] In order to facilitate public understanding, the technical solution and technical effects of the present invention are further described in detail below through specific embodiments:
[0060] Embodiment 1:
[0061] The welding core selected in this embodiment is a pure nickel welding core, and 100 parts are taken.
[0062] The mass percentages of the components of the medicinal powder of this embodiment are as follows:
[0063] Calcium fluoride 15 parts,
[0064] 1 part of sodium fluoroaluminate,
[0065] Calcium carbonate 18 parts,
[0066] 1 part strontium carbonate,
[0067] 1 part of lithium carbonate,
[0068] 1.5 parts of titanium oxide,
[0069] 2 parts of potassium titanate,
[0070] 5 parts of tungsten powder,
[0071] 2.5 parts of tungsten oxide (WO 3 :W 18 O 49 =2:1 mixture),
[0072] 2 parts of atomized ferrosilicon,
[0073] 2 parts of electrolytic manganese,
[0074] 8.5 parts of ferroniobium,
[0075] 11 parts of molybdenum powder,
[0076] 27 parts of metallic chromium,
[0077] 2 parts iron powder,
[0078] 0.1 part of graphite,
[0079] 1 part seaweed salt
[0080] Embodiment 2:
[0081] The welding core selected in this embodiment is the same as that in embodiment 1.
[0082] The mass percentages of the components of the medicinal powder of this embodiment are as follows:
[0083] Calcium fluoride 18 parts,
[0084] Potassium fluoroaluminate 2 parts,
[0085] Calcium carbonate 17 parts,
[0086] 1 part strontium carbonate,
[0087] 3 parts of titanium oxide,
[0088] 4 parts of potassium titanate,
[0089] 3.5 parts of tungsten powder,
[0090] 2 parts of tungsten oxide (WO 3 :W 20 O 58 =3:1 mixture),
[0091] 1 part of atomized ferrosilicon,
[0092] 4.5 parts of electrolytic manganese,
[0093] 6 parts of ferroniobium,
[0094] 9 parts of molybdenum powder,
[0095] 26.5 parts of metallic chromium,
[0096] 1.5 parts of iron powder,
[0097] 0.3 parts of graphite,
[0098] 1.2 parts of seaweed salt.
[0099] Embodiment 3:
[0100] The welding core selected in this embodiment is the same as that in embodiment 1.
[0101] The mass percentages of the components of the medicinal powder of this embodiment are as follows:
[0102] Calcium fluoride 16 parts,
[0103] Potassium fluoroaluminate 2 parts,
[0104] 15 parts of calcium carbonate,
[0105] 9 parts of barium carbonate,
[0106] 1 part of lithium carbonate,
[0107] 2.5 parts of titanium oxide,
[0108] 2.5 parts of potassium titanate,
[0109] 3 parts of tungsten powder,
[0110] 1.5 parts of tungsten oxide (WO 3 :WO 2 = 1:1 mixture),
[0111] 1.5 parts of atomized ferrosilicon,
[0112] 3.5 parts of electrolytic manganese,
[0113] 7.5 parts of ferroniobium,
[0114] 7 parts of molybdenum powder,
[0115] 26 parts of metallic chromium,
[0116] 1 part iron powder,
[0117] 0.5 parts of graphite,
[0118] 1 part seaweed salt
[0119] Manual electrodes with a diameter of φ3.2 mm were made for implementation cases 1-3 and cladding metal welding tests were carried out. The welding process parameters are shown in Table 2. The chemical composition and mechanical properties of the deposited metal were measured, as shown in Tables 3 and 4.
[0120] Table 2 Optimized welding process parameters of 9Ni steel electrodes for AC welding
[0121]
[0122] Table 3 Chemical composition of cladding metal of 9Ni steel electrode for optimized AC welding (mass percentage %)
[0123]
[0124] Table 4 Mechanical properties of cladding metal of 9Ni steel electrode for optimized AC welding
[0125]
[0126] It can be seen that compared with CN111590240A, the -196°C impact energy (J) of the present invention is significantly improved, with the highest value of CN111590240A being 91.7 and the lowest value of the present invention being 110.
[0127] Furthermore, the CN111590240A patent has the defect that the unstable arc easily causes poor fusion between the base material and the weld, and easily generates pores and slag inclusions.
Claims
1. A welding rod for 9Ni steel for AC welding, characterized in that: It consists of two parts: welding core and coating. The welding core part is a pure nickel welding core, and the coating part is composed of powder bonding; The components of the powder are by weight: 16%-20% fluoride; 20%-25% carbonate; 1%-5% titanium oxide; 2%-6% potassium titanate; 3%-5% tungsten powder; 1%-3% tungsten oxide; 1%-3% atomized ferrosilicon; 1%-6% electrolytic manganese; 5%-10% ferroniobium; 10%-15% molybdenum powder; 25%-28% metallic chromium; 1%-5% iron powder; 0.1%-0.6% graphite; 1%-3% seaweed salt.
2. A welding rod for 9Ni steel for AC welding as claimed in claim 1, characterized in that: The weight ratio of the coating to the electrode body is (3.5-4.5):
10.
3. A welding rod for 9Ni steel for AC welding as claimed in claim 1, characterized in that: The tungsten oxide is WO3, W 20 O 58 , W 18 O 49 , WO 2。 4. A welding rod for 9Ni steel for AC welding as claimed in claim 1, characterized in that: The fluoride is any one or more of calcium fluoride, sodium fluoroaluminate, and potassium fluoroaluminate.
5. A welding rod for 9Ni steel for AC welding as claimed in claim 1, characterized in that: The carbonate is any one or more of calcium carbonate, strontium carbonate, lithium carbonate and barium carbonate.
Citation Information
Patent Citations
Nickel-based welding electrode for low-spatter 9Ni steel
CN106181115A
9% Ni steel matched nickel-based welding rod special for overhead welding
CN111590240A
ENi6620 nickel-based welding rod for alternating current and preparation method and welding method thereof
CN113414519A
Nickel-based welding electrode matched with 9Ni steel
CN102500951A
Iron-based superalloy welding rod for 650 DEG C-grade ultra-supercritical power station boiler
CN113579560A
